Topology of the Magnetic Field and Resistivity of a Compact Torus Generated in a Mirrorless Theta Pinch - Kayama, Milton E. [UNESP]; Michelin, Thiago J. [UNESP]; Nascimento, Luiz C. (Springer Nature, 2019)
The mapping of the magnetic field and analysis of the plasma resistivity were used to study the change of magnetic field topology during the formation of a reversed field configuration. Using a theta pinch with straight coil, the formation of the torus was observed during the early time of the plasma radial implosion, in scale comparable to Alfvén’s time and shorter than the resistive diffusion. The non-intrusive excluded flux probe also indicated the formation of the torus even in the absence of mirror coils in the system. The plasma at the end region of the coil has distributed in the entire cross section of the tube, slightly peaked at the null field region. The anomalous plasma resistivity at the reconnection site was close to the prediction given by numerical calculation using numerical hybrid code with anomalous collision frequency either calculated using Chodura’s algorithm or evolution of microinstabilities, particularly the lower hybrid drift instability.
Keywords: FRC; Magnetic probe; PIC; Reconnection; Resistivity; Theta pinch